2002
DOI: 10.1046/j.1523-1739.2002.00381.x
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a New Wild Population of Tuatara (Sphenodon guntheri)

Abstract: Translocations of reptiles and amphibians have been questioned as a conservation tool because they generally have not been successful. However, translocation is the only method by which many species can be restored to parts of their former range, which increases their conservation security. Tuatara (  Sphenodon spp.), sole surviving members of the reptilian Order Sphenodontia, are restricted to offshore islands of New Zealand. Dispersal into former habitat on the mainland or other islands, following removal of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
137
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(139 citation statements)
references
References 24 publications
2
137
0
Order By: Relevance
“…The greatest chance for the future survival of tuatara, other than reducing the magnitude of global warming, lies in their translocation to other islands or protected mainland areas predicted to have thermally suitable micro-sites for nesting (Nelson et al 2002a). Several translocations aimed at restoring tuatara to parts of their former range have occurred since the mid-1990s, including three translocations of S. guntheri.…”
Section: Discussionmentioning
confidence: 99%
“…The greatest chance for the future survival of tuatara, other than reducing the magnitude of global warming, lies in their translocation to other islands or protected mainland areas predicted to have thermally suitable micro-sites for nesting (Nelson et al 2002a). Several translocations aimed at restoring tuatara to parts of their former range have occurred since the mid-1990s, including three translocations of S. guntheri.…”
Section: Discussionmentioning
confidence: 99%
“…Translocation has met with mixed success when applied to reptiles of conservation concern, but the successful establishment of translocated reptiles [e.g. Nelson et al, 2002b;Cook, 2004;Germano and Bishop, 2009] demonstrates that it could be an important tool for allowing species to persist under a changing climate. Translocation to more southern reserves has been proposed for the Brothers' Island tuatara (S. guntheri) as a means of mitigating the impact of climate change -in this case, translocated populations already occur for this species and proposed translocation sites are potentially within the species' historic range [Mitchell et al, 2008].…”
Section: How Should Populations At Risk Be Managed?mentioning
confidence: 99%
“…Small individuals with more ticks are more likely to be exposed to, and to ingest, an infective tick. Although tuatara have indeterminate growth, and size is not necessarily related to age (Nelson et al, 2002a), smaller individuals are probably younger than larger individuals and may be sufficiently naïve to the blood parasite to permit higher infection intensities. This is supported by the higher frequency of Ht observed in leukocytes among larger hosts.…”
Section: Host Size and Ht Infectionmentioning
confidence: 99%
“…However, we consider this explanation unlikely because bloodparasite infections in reptiles are rarely lethal (Eisen, 2001;Brown et al, 2006), and we found no association between blood-parasite infection and body condition. Furthermore, estimated annual survival rates of adult tuatara are relatively high (.95%; Nelson et al, 2002b).…”
Section: Host Size and Ht Infectionmentioning
confidence: 99%